A qualitative analysis of performance of student teachers with hearing impairments in tests and assignments at Kitwe College of Education-Zambia - Brighton Kumatongo; Kenneth Kapalu Muzata (Universitas Majalengka, 2022)
Assessment is the basis for understanding students’ abilities to demonstrate their knowledge, skills and understanding of learned concepts. This study sought to analyse assessment items of student teachers with hearing impairments at Kitwe Colleges of Education in Zambia and a qualitative case study was used as the research design. The study comprised seven (7) participants of which three (3) were Lecturers and four (4) were student teachers with hearing impairments, who were purposively sampled. The study revealed that students with hearing impairments were able to answer assignments accordingly despite exhibiting referencing and grammatical errors, and experienced more challenges answering tests. The findings also indicated that lecturers viewed the performance of student teachers with hearing impairments in assignments as being influenced by their hearing peers and that students with hearing impairments wrote their assignments and tests using sign language that was not making sense to lecturers. The study concluded that student teachers with hearing impairments were able to perform better in assignments and that they experienced more challenges answering test questions. The study recommended the need for assessment items for students with hearing impairments to be adapted to make them appropriate for the students and that educators for students with hearing impairments should take a keen interest in acquiring knowledge of Zambia Sign Language grammatical structure to enable them to assess and mark assessment items of students with hearing impairments without difficulties.